2016
DOI: 10.1177/0269215516680856
|View full text |Cite
|
Sign up to set email alerts
|

Home exercise programmes supported by video and automated reminders compared with standard paper-based home exercise programmes in patients with stroke: a randomized controlled trial

Abstract: The use of smart technology was not superior to standard paper-based home exercise programmes for patients recovering from stroke. This trial design was registered prospectively with the Australian and New Zealand Clinical Trials Register, ID: ACTRN 12613000786796. http://www.anzctr.org.au/trialSearch.aspx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 17 publications
4
92
0
1
Order By: Relevance
“…These findings are consistent with those reported by Gilmore and Spaulding who found greater satisfaction in participants who received video feedback during a functional task [4]. Furthermore, in a randomised controlled trial investigating adherence to exercise in people with stroke, Emmerson et al [24] compared paperbased home exercises to home exercises filmed on an electronic tablet. Whilst there were no significant between group differences in adherence, the authors stated that a potential benefit could be the accuracy of movement and feedback aspect of the video use and suggested that this may be evaluated in further studies.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with those reported by Gilmore and Spaulding who found greater satisfaction in participants who received video feedback during a functional task [4]. Furthermore, in a randomised controlled trial investigating adherence to exercise in people with stroke, Emmerson et al [24] compared paperbased home exercises to home exercises filmed on an electronic tablet. Whilst there were no significant between group differences in adherence, the authors stated that a potential benefit could be the accuracy of movement and feedback aspect of the video use and suggested that this may be evaluated in further studies.…”
Section: Discussionsupporting
confidence: 83%
“…This¯nding contrasted to the study of Emmerson et al which showed that home exercise programs¯lmed on an electronic tablet was not superior to standard paper-based home exercise programs in terms of adherence, motor function, or satisfaction for patients recovering from stroke. 12 There are several possible explanations for thesē nding, the adherence of home exercise may depend on the type of exercise and interest of patients. It was suggested that mobility decline is an essential concern in chronic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, evidence showed that home exercise prescription in paper-based format does not lead to better adherence to a home exercise program compared to having no written and pictorial instructions for patients with stroke less than four months. 10 The recent increasing accessibility of smart technology 11 o®ers an opportunity to advance the mode of delivery of home exercise program by mobile devices such as video-guided exercise on electronic tablets 12 and video-guided exercise on mobile apps. 13 However, the e®ects of mobile video-guided exercise programs were controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design framework was based on phenomenology to understand the lived experience of each individual (Liampputong, 2013) utilising this technology for their rehabilitation. Using convergent mixed methods, the results of the qualitative analysis were triangulated with quantitative results that have been reported elsewhere (Emmerson et al, 2016).…”
Section: Designmentioning
confidence: 99%